Free Marine Natural Products Databases for Biotechnology and Bioengineering. Issue 11 (8th August 2019) - Barbosa, Arménio J. M.; Roque, Ana C. A.
Abstract : Marine organisms and micro‐organisms are a source of natural compounds with unique chemical features. These chemical properties are useful for the discovery of new functions and applications of marine natural products (MNPs). To extensively exploit the potential implementations of MNPs, they are gathered in chemical databases that allow their study and screening for applications of biotechnological interest. However, the classification of MNPs is currently poor in generic chemical databases. The present availability of free‐access‐focused MNP databases is scarce and the molecular diversity of these databases is still very low when compared to the paid‐access ones. In this review paper, the current scenario of free‐access MNP databases is presented as well as the hindrances involved in their development, mainly compound dereplication. Examples and opportunities for using freely accessible MNP databases in several important areas of biotechnology are also assessed. The scope of this paper is, as well, to notify the latent potential of these information sources for the discovery and development of new MNPs in biotechnology, and push future efforts to develop a public domain MNP database freely available for the scientific community. Abstract : Marine organisms and micro‐organisms are a natural source of compounds with unique chemical features, applied in drug discovery, cosmetics, materials, and production of biofuels. As the discovery of new marine natural products (MNPs) growths, the current state of the art on MNP databases, access and exploitation of this information, is addressed in this mini‐review.